An anaplastic cardiac large cell lymphoma: a case report and analysis of cardiac involvement in newly diagnosed non-Hodgkin's lymphoma from the Czech Lymphoma Study Group (CLSG) database - Lobello, Cosimo; Janikova, Andrea; Kren, Leos; Hermanova, Marketa; Sprlakova-Pukova, Andrea; Krejci, Jan; Pospisilova, Sarka; Pytlik, Robert; Hamouzova, Michaela; Belada, David; Prochazka, Vit; Duras, Juraj; et al. (Journal of cancer research and therapeutics, 2017)
We report a rare case of anaplastic large cell ALK+ lymphoma (ALCL) with initial asymptomatic cardiac involvement. A 59-year-old male with infiltration of the right ventricular wall underwent standard combined chemotherapy (CHOP) and achieved remission without significant cardiac impairment. Additionally, we report the actual incidence of cardiac lymphoma in newly diagnosed non-Hodgkin Lymphomas (NHLs). In total, 16 patients with cardiac lymphoma were found (0.1% NHLs) in the Czech Lymphoma Study Group database. DLBCL was the most frequent histology subtype (50%), and ALCL was identified in 12.5% of cases. At initial diagnosis, the median age was 55.5 (range 21-74) years and 59% were men. None of the 16 patients with cardiac involvement had isolated heart lymphoma. The response to first-line therapy was 79% in 14/16 evaluable patients. The median progression-free survival and overall survival were nearly the same – approximately 3.5 years (range; 0.05-16.7ys), while the median follow up was 4 years.
Keywords: Heart Neoplasms; rizikové faktory; nádory srdce; Humans; mužské pohlaví; Male; lidé; Middle Aged; lidé středního věku; anaplastický velkobuněčný lymfom; Lymphoma, Large-Cell, Anaplastic; Risk Factors